Compacted lithium iron manganese phosphate positive electrode material and preparation method thereof
By using strontium carbonate and boric acid flux in the preparation of lithium manganese iron phosphate positive electrode material, and combined with di-fired CVD carbon-encapsulated process, the problem of low material compaction density is solved, and the preparation of materials with high compaction density, low specific surface area and high conductivity is achieved, improving the energy density and performance of the battery.
Patent Information
- Application Number
- CN202411928183.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-25
AI Technical Summary
The compaction density of existing lithium manganese iron phosphate cathode materials is low, resulting in high specific surface area and poor processing performance, affecting the actual energy density of the battery and limiting its promotion and application.
The binary composite flux of strontium carbonate and boric acid is used to molten during high-temperature calcination to improve the uniformity of manganese manganese and iron mixture, and the compaction and electrochemical properties of the material are improved through the di-sintered chemical vapor deposition process.
A lithium manganese iron phosphate positive electrode material with high compaction density, low specific surface area and high conductivity was prepared. The charging capacity and discharge capacity were significantly improved, and the compaction density reached 2.43g/cm3, which was suitable for practical applications of batteries.
Smart Images

Figure CN119764442A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery positive electrode materials, and in particular to a compacted lithium manganese iron phosphate positive electrode material and a preparation method thereof. Background Art
[0002] Lithium iron manganese phosphate is an upgraded product of lithium iron phosphate. Manganese replaces the iron lattice site, which greatly improves the average discharge voltage of the material. The overall energy density is 15-20% higher than that of lithium iron phosphate. However, compared with lithium iron phosphate, an obvious shortcoming of lithium iron manganese phosphate is its lower electrical conductivity and ion diffusion coefficient. Therefore, it is usually necessary to nano-size and carbon-coate the material to improve its comprehensive electrochemical performance. However, the disadvantage of this is that the compaction density of the material will be greatly reduced.
[0003] CN118164456A discloses a method for preparing a lithium iron manganese phosphate-carbon composite material, comprising: (1) adding manganese phosphate, a lithium source, a carbon source, and deionized water in a set ratio into a stirrer, and mixing them evenly to obtain a solution A; (2) adding iron phosphate powder into the solution A, and dispersing them evenly to obtain a suspension B; (3) placing the suspension B in a high-pressure reactor for hydrothermal treatment, solid-liquid separation, and obtaining a precursor; (4) placing the precursor in an inert atmosphere for calcination, and grinding after cooling to obtain the lithium iron manganese phosphate-carbon composite material. The lithium iron manganese phosphate-carbon composite material provided by this prior art significantly improves the electronic conductivity and cycle stability of the material, but does not mention the compaction density of the material.
[0004] The compaction density of commercial lithium iron phosphate is usually 2.5g / cm 3 Above, even close to 2.6g / cm 3 , while commercial lithium manganese iron phosphate has only 2.2-2.3g / cm 3 On the one hand, it causes the lithium manganese iron phosphate material to have a higher specific surface area and poorer processing performance. On the other hand, it also causes the actual energy density of the battery to drop sharply, thus affecting the promotion and application of lithium manganese iron phosphate batteries. Summary of the invention
[0005] The purpose of the present invention is to solve the technical problems in the prior art, and to prepare a high-performance lithium iron manganese phosphate positive electrode material through two technical means. The material has the characteristics of high compaction, low specific surface area, high capacity and high conductivity:
[0006] First, the present invention proposes a new synthesis method for compacted manganese iron phosphate lithium positive electrode material. This method uses manganese phosphate, iron phosphate and lithium phosphate as raw materials, and under the action of strontium carbonate and boric acid binary composite flux, prepares excellent performance manganese iron phosphate lithium with high compaction density. The role of strontium carbonate is to flux during high-temperature calcination, greatly improving the uniformity of manganese iron mixing, thereby improving the final performance. Boric acid can not only flux, but also improve the ionic conductivity of the material, so that the final electrochemical performance is greatly increased.
[0007] Secondly, through the unique two-firing chemical vapor deposition (CVD) carbon coating process, the compaction performance of the material is further improved while the discharge capacity is also greatly increased.
[0008] Specifically, the present invention adopts the following technical solutions:
[0009] On the one hand, the present invention provides a method for preparing a compacted lithium iron manganese phosphate positive electrode material, which comprises: using iron phosphate, manganese phosphate, and lithium phosphate as raw materials, adding strontium carbonate and boric acid, spray drying, and then calcining to obtain a compacted lithium iron manganese phosphate positive electrode material.
[0010] Furthermore, the preparation method includes the following steps: S1. Evenly mix iron phosphate, manganese phosphate and lithium phosphate in an aqueous solution to obtain a suspension dispersion; S2. Add strontium carbonate to the suspension dispersion, mix well and then add boric acid to obtain a mixed slurry; S3. Spray dry the mixed slurry and then calcine it to obtain a compacted manganese iron phosphate lithium positive electrode material.
[0011] Furthermore, step S1 also has at least one of the following technical features:
[0012] (1) The atomic number ratio of Li, P, Mn, and Fe in iron phosphate, manganese phosphate, and lithium phosphate is (1-1.05):1:(0.5-0.9):(0.1-0.5);
[0013] (2) a carbon source I and / or a dopant are also added, that is, the suspension dispersion also includes a carbon source I and / or a dopant;
[0014] Wherein, the carbon source I is selected from at least one of glucose, sucrose, PEG, PVA, asphalt, cellulose, and starch;
[0015] The dopant is selected from at least one of titanium oxide, magnesium oxide, niobium oxide, aluminum oxide, zirconium oxide, copper oxide, zinc oxide, sodium carbonate and potassium carbonate; preferably, the dopant is nano titanium dioxide and nano magnesium dioxide.
[0016] In the present invention, the carbon source I acts as a protective agent and a coating carbon. If the carbon source I is not added, the product is easily oxidized in the air or during high-temperature calcination.
[0017] In a specific embodiment of the present invention, the amount of carbon source I added is such that the mass ratio of carbon to the raw material is 5-10%, wherein "raw material" refers to iron phosphate, manganese phosphate, lithium phosphate, strontium carbonate, boric acid, carbon source I, and optionally a dopant.
[0018] In a specific embodiment of the present invention, the dopant is titanium dioxide and magnesium dioxide, wherein the proportion of titanium in titanium dioxide in the raw material is 500-10000ppm, and the proportion of magnesium in magnesium oxide in the raw material is 500-10000ppm, wherein "raw material" refers to iron phosphate, manganese phosphate, lithium phosphate, strontium carbonate, boric acid, dopant, and optionally carbon source I.
[0019] In a specific embodiment of the present invention, step S1 is:
[0020] Add carbon source I into deionized water and stir until dissolved, then add iron phosphate, manganese phosphate and lithium phosphate in sequence. At this time, trace bubbles are generated in the solution. Stir the solution at the same stirring rate until it turns dark purple. Finally, add the dopant and stir evenly to obtain a suspension dispersion.
[0021] Furthermore, step S2 also has at least one of the following technical features:
[0022] (1) The proportion of strontium in strontium carbonate in the raw material is 100-8000ppm; preferably 1000-2000ppm;
[0023] (2) The proportion of boron in boric acid in the raw material is 100-8000 ppm; preferably 1000-2000 ppm;
[0024] (3) The solid content of the mixed slurry is 25-35%;
[0025] Herein, “raw materials” refer to iron phosphate, manganese phosphate, lithium phosphate, strontium carbonate, boric acid, and optionally a carbon source I and a dopant.
[0026] In a specific embodiment of the present invention, step S2 is:
[0027] Strontium carbonate was added to the suspension dispersion, and after being stirred evenly, the suspension was put into a sand mill for sand grinding until the slurry D50 was within the range of 100-500 nm, and then boric acid was added to continue sand grinding for a period of time.
[0028] Furthermore, step S3 is specifically as follows:
[0029] S31. The mixed slurry is spray dried to obtain a yellow material sample;
[0030] S32. The yellow material sample is calcined for the first time to obtain lithium manganese iron phosphate black material I;
[0031] S33. The lithium manganese iron phosphate black material I and the carbon source II are mixed to obtain a suspension;
[0032] S34. After spray drying the suspension, calcining is performed for the second time to obtain a compacted lithium manganese iron phosphate positive electrode material.
[0033] In a specific embodiment of the present invention, in step S31, the inlet temperature of the spray drying is 150-250°C, the outlet temperature is 70-100°C, the feed rate is 3-12mL / min, the outlet temperature is controlled to be stable according to the viscosity of the slurry and the feed rate, and finally the spray-dried yellow material sample is collected in a sample collection bottle.
[0034] In a specific embodiment of the present invention, in step S32, the yellow material sample is added to a graphite crucible, vibrated, and placed in a box furnace for calcination. Before heating, it is necessary to evacuate and introduce high-purity nitrogen. After repeating 3-5 times, the vent valve is reduced and N is slowly introduced. 2 , N 2 The flow rate is adjusted to 2-10 mL / min, the heating rate is 1-10° C. / min, the calcination temperature is 650-800° C., the calcination time is 5-10 h, and after naturally cooling to room temperature, lithium manganese iron phosphate black material I is obtained.
[0035] In a specific embodiment of the present invention, in step S33, the carbon source II is selected from at least one of glucose, sucrose, PEG, PVA, asphalt, cellulose, and starch; and the amount of carbon source II added is such that the mass ratio of carbon to the raw material is 2-8%.
[0036] In a specific embodiment of the present invention, the temperature of the first calcination and the second calcination are independently 650-800° C., and the time is 3-10 h.
[0037] Preferably, the first calcination temperature is 650-700° C. and the time is 6-10 h.
[0038] Preferably, the second calcination temperature is 700-780° C. and the time is 3-6 hours.
[0039] In a specific implementation of the present invention, step S34 is specifically:
[0040] The suspension is spray-dried to obtain lithium manganese iron phosphate black material II;
[0041] The lithium iron manganese phosphate black material II is calcined for the second time to obtain the lithium iron manganese phosphate black material III;
[0042] The lithium iron manganese phosphate black material III is crushed multiple times to obtain the lithium iron manganese phosphate black material IV.
[0043] In a specific embodiment of the present invention, in S34, the solid content of the suspension is 35-45%.
[0044] In a specific embodiment of the present invention, in S34, the inlet temperature of the spray drying is 150-250°C, the outlet temperature is 70-100°C, the feed rate is between 3-12 mL / min, the outlet temperature is controlled to be stable according to the viscosity of the slurry and the feed rate, and finally the spray-dried lithium manganese iron phosphate black material II is collected in a sample collection bottle.
[0045] In a specific embodiment of the present invention, a gaseous carbon source III is also included in the second calcination process;
[0046] Preferably, the carbon source III is selected from at least one of acetylene, methane, ethane and butane.
[0047] In a specific embodiment of the present invention, in S34, lithium manganese iron phosphate black material II is weighed and added to a graphite crucible, compacted, and placed in a box furnace for calcination. Before heating, it is necessary to evacuate and introduce high-purity nitrogen. After repeating 3-5 times, the vent valve is reduced and the gaseous carbon source III and N are slowly introduced. 2 The mixed gas has a ratio of (1:99)-(99:1), a gas flow rate of 2-10mL / min, a heating rate of 1-10℃ / min, a calcination temperature of 650-800℃, a calcination time of 5-10h, and after naturally cooling to room temperature, lithium manganese iron phosphate black material III is obtained.
[0048] The present invention adopts CVD gas phase carbon deposition technology, that is, carbon coating is performed by cracking and depositing a gaseous carbon source III at high temperature. This method can improve the uniformity of the coating, thereby greatly improving the powder conductivity of the material, improving the morphology of the material surface, and also playing a role in increasing the compaction density.
[0049] In a specific embodiment of the present invention, in S34, the lithium iron manganese phosphate black material III is placed in an air flow pulverizer for multiple crushing until its D50 particle size reaches 1-5 μm, thereby obtaining the lithium iron manganese phosphate black material IV, that is, the target product compacted lithium iron manganese phosphate positive electrode material.
[0050] On the other hand, the present invention provides a compacted lithium manganese iron phosphate positive electrode material obtained by the aforementioned preparation method.
[0051] Compared with the prior art, the present invention has at least the following beneficial effects:
[0052] (1) The compacted lithium manganese iron phosphate positive electrode material obtained by the preparation method provided by the present invention has the characteristics of high capacity, high compaction, low specific surface area and high conductivity. Specifically, the compacted lithium manganese iron phosphate positive electrode material has a charging capacity of up to 161 mAh / g, a discharge capacity of up to 156 mAh / g, and a compaction density of up to 2.43 g / cm 3 , with a specific surface area of less than 15m 2 / g.
[0053] (2) The raw materials used in the present invention do not contain other impurity elements, and subsequent steps do not require impurity removal, thereby avoiding the impact of impurities on the performance of lithium-ion battery products. The method of the present invention can achieve uniform mixing of Mn / Fe / P, inhibit the Jan-Taylor effect, and improve the compaction density of the material without affecting the electrochemical properties of the material.
[0054] (3) The present invention adopts a binary composite flux of strontium carbonate and boric acid, wherein strontium carbonate decomposes into strontium oxide at high temperature, and strontium oxide reduces the melting temperature of manganese phosphate, iron phosphate and lithium phosphate during the crystallization process, thereby achieving melt crystallization at a relatively low temperature, reducing holes and defects during the crystallization process, and promoting the growth of lithium iron manganese phosphate crystals. Boric acid reacts with lithium carbonate and the like at high temperature to form a lithium metaborate compound with a relatively low melting point, which can play a good lubricating role in the solution, reduce the friction resistance between lithium phosphate, iron phosphate and manganese phosphate, improve fluidity, and help the three to mix evenly and react completely. The binary composite flux complements each other and acts synergistically to prepare a highly compacted lithium iron manganese phosphate sample. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 A schematic diagram of a process flow for preparing a compacted lithium manganese iron phosphate positive electrode material provided in Example 1 of the present invention;
[0056] Figure 2 The charge and discharge curves of the compacted lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention at different rates;
[0057] Figure 3 The cycle performance of the compacted lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention at a current of 0.33C;
[0058] Figure 4 This is a SEM image of the compacted lithium manganese iron phosphate positive electrode material prepared in Example 1 of the present invention (with flux added);
[0059] Figure 5 This is a SEM image of lithium manganese iron phosphate prepared in Comparative Example 1 of the present invention (without adding flux). DETAILED DESCRIPTION
[0060] Based on the problems in the prior art, the inventors found that the two-sintering process can effectively improve the compaction density of lithium manganese iron phosphate in the process of using iron phosphate, manganese phosphate and lithium phosphate as raw materials, but the electrochemical performance still cannot meet the requirements. After a lot of research, the inventors found that improving the uniformity of Mn / Fe / P can suppress the Jan-Taylor effect, thereby improving the compaction density of the material. Therefore, the inventors conducted a lot of experiments on how to improve the uniformity of Mn / Fe / P. Finally, it was found that during the high-temperature calcination process, if a flux is added, the melting temperature of the raw materials can be reduced, thereby improving the uniformity of the Mn / Fe / P mixture, and improving the compaction density of the material without affecting the electrochemical performance of the material.
[0061] In the present invention, strontium carbonate, as a salt, needs to be added first and mixed and dispersed more evenly; boric acid, as an acid, will affect the pH of the slurry system and reduce the stability of the slurry if added too early, so boric acid needs to be added after strontium carbonate is mixed, and boric acid is easily soluble and relatively easy to disperse.
[0062] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0063] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0064] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0065] The present invention provides a method for preparing compacted lithium manganese iron phosphate, which specifically comprises the following steps:
[0066] (1) Add carbon source I to deionized water and stir until dissolved, then add iron phosphate, manganese phosphate and lithium phosphate in sequence. At this time, trace bubbles are generated in the solution. Stir the solution at the same stirring rate until it turns dark purple. Finally, add the dopant and stir evenly to obtain a suspension dispersion with a solid content of 25-35%.
[0067] (2) Strontium carbonate is added to the above suspension dispersion, stirred evenly, and then put into a sand mill for sand grinding until the slurry D50 is in the range of 100-500nm, and then boric acid is added and sand grinding is continued for a period of time to obtain a mixed slurry.
[0068] (3) The mixed slurry is spray-dried, and the outlet temperature is controlled to be stable according to the viscosity and feed rate of the slurry to obtain a yellow material sample.
[0069] (4) The yellow material sample is calcined for the first time under an inert atmosphere, with a heating rate of 1-10°C / min, a calcination temperature of 650-800°C, and a calcination time of 5-10h. After naturally cooling to room temperature, lithium manganese iron phosphate black material I is obtained.
[0070] (5) The above-mentioned lithium manganese iron phosphate black material I and carbon source II are added to deionized water and mixed, and then sand-milled until the slurry D50 is in the range of 100-500 nm, and a suspension with a solid content of 35-45% is obtained.
[0071] (6) The suspension is spray-dried, and the outlet temperature is controlled to be stable according to the viscosity of the slurry and the feed rate to obtain lithium manganese iron phosphate black material II.
[0072] (7) The above-mentioned lithium iron manganese phosphate black material II is calcined for the second time under an inert atmosphere, and a carbon source III is introduced at the same time for CVD vapor phase carbon deposition. The heating rate is controlled to be 1-10°C / min, the calcination temperature is 650-800°C, the calcination time is 5-10h, and the temperature is naturally cooled to room temperature to obtain lithium iron manganese phosphate black material III.
[0073] (8) The above-mentioned lithium iron manganese phosphate black material III is crushed multiple times until its D50 particle size reaches 1-5 μm to obtain lithium iron manganese phosphate black material IV, that is, the target product compacted lithium iron manganese phosphate positive electrode material.
[0074] The present invention is further described in detail below through specific embodiments.
[0075] Example 1
[0076] Add 700mL of deionized water to a 2000mL beaker, add 40g of glucose, stir magnetically at a rate of 8000r / min until dissolved. Weigh iron phosphate, manganese phosphate and lithium phosphate according to the atomic ratio Li:P:Mn:Fe=1.03:1:0.6:0.4. Add iron phosphate powder to the beaker and continue stirring at a rate of 800r / min until it is dispersed more evenly. At the same stirring rate, add manganese phosphate powder and stir until the powder is evenly dispersed. Then gradually add lithium phosphate powder. At this time, the solution has trace bubbles. Stir at the same stirring rate until the solution is dark purple and evenly dispersed, then add 0.44g of nano titanium dioxide and 0.28g of nano magnesium dioxide to obtain a suspension dispersion.
[0077] Strontium carbonate was added to the suspension dispersion, the ratio of strontium to the raw material was 2000ppm, and the mixture was stirred at a speed of 800r / min for 2h. Then the suspension dispersion was added to the clean sand mill for sand grinding at a speed of 1000r / min for 10min, and then at 3000r / min for 60min. After the sand grinding, the particle size was measured by Malvern 3000 until the slurry D50 was 300nm. Boric acid was then added, the ratio of boron to the raw material was 1000ppm, and the sand grinding was continued for 2min to obtain a mixed slurry, at which the solid content of the slurry was 30%.
[0078] The mixed slurry was transferred to a beaker and spray dried using a spray dryer. The inlet temperature was adjusted to 220°C, the outlet temperature was controlled to 90°C, and the feed rate was controlled to be between 10mL / min. The outlet temperature was controlled to be stable according to the viscosity of the slurry and the feed rate. Finally, the spray-dried yellow material sample was collected in a sample collection bottle.
[0079] Weigh 100 g of the yellow material sample, add it to a graphite crucible, shake it, and put it into a box furnace for calcination. Before heating, vacuumize and introduce high-purity nitrogen. Repeat 3-5 times, then reduce the vent valve and slowly introduce N 2 , N 2 The flow rate was adjusted to 5 mL / min, the heating rate was 3°C / min, the calcination temperature was 650°C, the calcination time was 10 h, and after naturally cooling to room temperature, lithium manganese iron phosphate black material I was obtained.
[0080] Weigh 80 g of lithium manganese iron phosphate black material I sample, add it to a 1000 mL beaker, add 250 mL of deionized water, and then add 8 g of glucose. After stirring for half an hour, a black suspension is obtained. The suspension is added to a clean sand mill for sand grinding at a speed of 800 r / min for 10-100 min, and then at 3000 r / min for 30 min. After the sand grinding is completed, the particle size is measured by Malvern 3000 until the slurry D50 is 500 nm. At this time, the solid content of the suspension is 40%.
[0081] The suspension was transferred to a beaker and spray dried using a spray dryer. The inlet temperature was adjusted to 150°C, the outlet temperature was controlled to 75°C, and the feed rate was controlled to 10 mL / min. The outlet temperature was controlled to be stable according to the viscosity of the slurry and the feed rate. Finally, the spray-dried lithium manganese iron phosphate black material II was collected in a sample collection bottle.
[0082] Weigh 80 g of the above-mentioned lithium manganese iron phosphate black material II, add it into a graphite crucible, vibrate it, and put it into a box furnace for calcination. Before heating, it is necessary to evacuate the vacuum and introduce high-purity nitrogen. After repeating 3-5 times, reduce the ventilation valve and slowly introduce acetylene and N 2 Mixed gas (5:95), gas flow rate was adjusted to 3 mL / min, heating rate was 3°C / min, calcination temperature was 780°C, calcination time was 3 h, and after naturally cooling to room temperature, lithium manganese iron phosphate black material III was obtained.
[0083] In this embodiment, the chemical reaction equation is:
[0084] 6FePO 4 +9 MnPO 4 +5 Li 3 PO 4 +10C=15LiMn 0.6 Fe 0.4 PO 4 +10 CO 2 ↑
[0085] Example 2
[0086] The difference between this embodiment and embodiment 1 is that the atomic number ratio of iron phosphate, manganese phosphate and lithium phosphate is Li:P:Mn:Fe=1:1:0.6:0.4, and the other operations remain unchanged.
[0087] Example 3
[0088] The difference between this embodiment and embodiment 1 is that the mass of strontium is halved, that is, the proportion of strontium in the raw material is 1000 ppm, and the other operations remain unchanged.
[0089] Example 4
[0090] The difference between this embodiment and embodiment 1 is that the mass of boron is halved, that is, the proportion of boron in the raw material is 500 ppm, and the other operations remain unchanged.
[0091] Example 5
[0092] The difference between this embodiment and embodiment 1 is that the temperature of the first firing is adjusted to 700° C., and the other operations remain unchanged.
[0093] Example 6
[0094] The difference between this embodiment and embodiment 1 is that the temperature of the second calcination is adjusted to 800° C., and the other operations remain unchanged.
[0095] Example 7
[0096] The difference between this embodiment and embodiment 1 is that no carbon source III acetylene is added.
[0097] Comparative Example 1
[0098] The difference between this comparative example and Example 1 is that neither of the two fluxes is added.
[0099] Comparative Example 2
[0100] The difference between this comparative example and Example 1 is that no strontium carbonate is added.
[0101] Comparative Example 3
[0102] The difference between this comparative example and Example 1 is that no boric acid is added.
[0103] The performance of the lithium manganese iron phosphate obtained in the above examples and comparative examples was tested, and the test method adopted the group standard "Lithium manganese iron phosphate positive electrode material for lithium ion battery" T / CIAPS0029-2023. The test results are shown in Table 1:
[0104] Table 1 Performance test results of lithium manganese iron phosphate obtained in Examples 1 to 7 and Comparative Examples 1 to 3
[0105]
[0106] It can be seen from the table that the lithium manganese iron phosphate obtained by the method of the present invention has excellent electrical properties and high compaction density. In Comparative Example 1, no flux was used, resulting in the inability to evenly mix Mn / Fe / P, so the compaction density was the worst. Figure 4 and 5 It can be seen from the comparison that after adding flux, the material exhibits a structure similar to that of a single crystal, with a significantly smoother surface, clear edges and corners, and a uniform mix of large and small particles, which are all conducive to improving the compaction density. At the same time, it will also reduce the specific surface area of the material. The surface of the sample material without flux is obviously rough, the small particles are not tightly packed, and the material has many voids and defects, which is not conducive to improving the compaction density of the material.
[0107] In Comparative Examples 2 and 3, only boric acid or strontium carbonate flux was added, and the compaction density was significantly reduced, and the discharge performance was also significantly reduced.
[0108] In Comparative Example 4, the CVD carbon coating method is not used, and the compaction density and discharge capacity are slightly reduced, but the powder resistivity of the material is significantly increased, which is not conducive to rapid charging and discharging.
[0109] The specific embodiments of the present invention are described in detail above. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.
[0110] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0111] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
Claims
1. A method for preparing a compacted lithium manganese iron phosphate positive electrode material, characterized in that: The preparation method comprises: taking iron phosphate, manganese phosphate and lithium phosphate as raw materials, adding strontium carbonate and boric acid, spray drying, and then calcining to obtain the compacted manganese iron lithium phosphate positive electrode material.
2. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: S1. The iron phosphate, manganese phosphate and lithium phosphate are uniformly mixed in an aqueous solution to obtain a suspension dispersion; S2. adding strontium carbonate to the suspension dispersion, mixing and then adding boric acid to obtain a mixed slurry; S3. The mixed slurry is spray-dried and then calcined to obtain the compacted lithium manganese iron phosphate positive electrode material.
3. The preparation method according to claim 2, characterized in that: In S1, the atomic number ratio of Li, P, Mn and Fe in the iron phosphate, manganese phosphate and lithium phosphate is (1-1.05):1:(0.5-0.9):(0.1-0.5).
4. The preparation method according to claim 2, characterized in that: In S1, a carbon source I and / or a dopant are also added, that is, the suspension dispersion also includes a carbon source I and / or a dopant; Preferably, the carbon source I is selected from at least one of glucose, sucrose, PEG, PVA, asphalt, cellulose, and starch; Preferably, the dopant is selected from at least one of titanium oxide, magnesium oxide, niobium oxide, aluminum oxide, zirconium oxide, copper oxide, zinc oxide, sodium carbonate and potassium carbonate.
5. The preparation method according to claim 2, characterized in that: In S2, the proportion of strontium in the strontium carbonate in the raw material is 100-8000ppm; Preferably, the proportion of boron in the boric acid in the raw material is 100-8000 ppm.
6. The preparation method according to claim 2, characterized in that: The S3 is specifically: S31. The mixed slurry is spray-dried to obtain a yellow material sample; S32. The yellow material sample is calcined for the first time to obtain lithium manganese iron phosphate black material I; S33. The lithium iron manganese phosphate black material I is mixed with the carbon source II to obtain a suspension; S34. After spray drying the suspension, calcining it for the second time to obtain the compacted lithium manganese iron phosphate positive electrode material.
7. The preparation method according to claim 6, characterized in that: The carbon source II is selected from at least one of glucose, sucrose, PEG, PVA, asphalt, cellulose, and starch; Preferably, the first calcination and the second calcination are both carried out at a temperature of 650-800° C. and for a time of 3-10 h.
8. The preparation method according to claim 6, characterized in that: The step S34 is specifically as follows: The suspension is spray-dried to obtain lithium manganese iron phosphate black material II; calcining the lithium iron manganese phosphate black material II for a second time to obtain the lithium iron manganese phosphate black material III; The lithium iron manganese phosphate black material III is crushed multiple times to obtain the lithium iron manganese phosphate black material IV, which is the compacted lithium iron manganese phosphate positive electrode material.
9. The preparation method according to claim 8, characterized in that: During the second calcination process, a carbon source III is also introduced; Preferably, the carbon source III is selected from at least one of acetylene, methane, ethane and butane.
10. The compacted lithium manganese iron phosphate positive electrode material obtained according to the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method and application of lithium ferric manganese phosphate-carbon composite material
CN118164456A
Lithium ion battery cathode material and preparation method thereof
CN105449197A
Preparation method of lithium iron phosphate with high compaction density and high capacity
CN110098406A
Preparation method of lithium iron phosphate with high compaction density
CN115092903A
Composite doped high-nickel large-single-crystal ternary layered oxide positive electrode material and preparation method and application thereof
CN115763749A